Upaya Penanganan Konstipasi Pada Ibu Hamil Trimester III Di Puskesmas Grogol Sukoharjo - DWI SULISTIYOWATI, YUNITA, Winarsih Nur Ambarwati, S.Kep,Ns,ETN,MKep (2016)
Background : Pregnancy is a physiological occurrence and it should be realized that all pregnant women . During pregnancy , a woman's body will undergo many changes . Good physical changes, mood , and hormonal . Of course all can cause a variety of complaints and issues in the third trimester of pregnancy one of which is constipation . The incidence of constipation in pregnant women ranging from 11 % to 38 % , resulting from a decrease of the intestinal peristalsis result of an increase in the hormone progesterone. Objective : to deal with constipation in the third trimester pregnant women in accordance with the standards of nursing care. Methods : The method used is descriptive in Ny.N with a case study approach , is to perform nursing care ranging from assessment , intervention , implementation and evaluation. Results : After 3 days of nursing care during home visits diagnosis that appears on Ny.N are constipation are associated with increased production of the hormone progesterone , inadequate intake of fiber , fluids and exercise. Conclusion : The problem of nursing that occur on the client is resolved in part so that the intervention should be continued.